2018
DOI: 10.1159/000486598
|View full text |Cite
|
Sign up to set email alerts
|

Non-Urothelial Bladder Cancer: Comparison of Clinicopathological and Prognostic Characteristics in Pure Adenocarcinoma and Non-Bilharzial Squamous Cell Carcinoma of the Bladder

Abstract: Objectives: The clinicopathological characteristics, treatment modalities, and effects on the prognosis of pure squamous cell carcinoma (SqCC) and adenocarcinoma (AC) were evaluated. Materials and Methods: 86 patients with pure SqCC and AC bladder cancer were evaluated retrospectively. Results: Of the 86 patients, 51 had SqCC and 35 had AC. No differences in clinicopathological characteristics were observed between patients with AC and SqCC, except for the prevalence of T4 disease (28.6% vs. 51.0%, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The patient was found to have an occupying bladder lesion on physical examination and was admitted with only mild urinary frequency and no meatus hematuria. On the other hand, SCC patients with T3/4 disease usually exhibit a lower rate of lymph node metastases (10%–25%) and distant metastases (8%–27.7%) ( 20 ). This case is consistent with the report of ERDEM, which showed no lymph node invasion and pelvic metastasis on CT 10 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…The patient was found to have an occupying bladder lesion on physical examination and was admitted with only mild urinary frequency and no meatus hematuria. On the other hand, SCC patients with T3/4 disease usually exhibit a lower rate of lymph node metastases (10%–25%) and distant metastases (8%–27.7%) ( 20 ). This case is consistent with the report of ERDEM, which showed no lymph node invasion and pelvic metastasis on CT 10 years ago.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in patients with BSCC, neoadjuvant chemotherapy prior to radical cystectomy did not confer a survival benefit. Previous studies 8,[10][11][12] found that BSCC patients were less sensitive to chemotherapy and more prone to chemotherapy resistance when compared with UC patients. This may also explain that the proportion of receiving chemotherapy in BSCC patients is lower than that in UC patients.…”
Section: Survival Analysismentioning
confidence: 93%